5DP-130 TO INCREASE WORK PRODUCTIVITY BY IMPROVING THE WORK CHAMBER OF THE CHAIN SAW. (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
In production, we mainly use a sawmill to extract cotton from seeds. By improving the 5DP-130 sawing machine, by installing a cylindrical shaft in the central part of the raw material shaft, in order to ensure that the density of the raw material shaft does not increase in the working chamber of the sawing machine, to achieve an increase in work efficiency.